Genetically modified white maize in South Africa : consumer perceptions and market segmentation - Schonfeldt, H.C. (Hettie Carina) (University of Pretoria, 2013)
Dissertation (MSc (Agric) Agricultural Economics)--University of Pretoria, 2004.